2023
DOI: 10.1002/jez.b.23194
|View full text |Cite
|
Sign up to set email alerts
|

Chicken HOXC8 and HOXC10 genes may play a role in the altered skull morphology associated with the Crest phenotype

Abstract: One of the most intriguing traits found in domestic chickens is the Crest phenotype. This trait, characterized by a tuft of elongated feathers sprouted from the head, is found in breeds such as Polish chickens and Silkie chickens. Moreover, some crested chicken breeds also exhibit a protuberance in their anterodorsal skull region. Previous studies have strived to identify the causative factors of this trait. This study aimed to elucidate the role of chicken HOXC8 and HOXC10 in the formation of the Crest phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…The crest is a cluster of feathers protruding from the head that are widely present in various birds, but the morphology of the crest varies among different birds. Research on crested chickens has shown that the HOX genes play a role in the formation of the altered skull morphology related to the crest phenotype [40]. The gene controlling the chicken crest trait may be located in the HOXC cluster adjacent to the HOXC8 gene [41].…”
Section: Discussionmentioning
confidence: 99%
“…The crest is a cluster of feathers protruding from the head that are widely present in various birds, but the morphology of the crest varies among different birds. Research on crested chickens has shown that the HOX genes play a role in the formation of the altered skull morphology related to the crest phenotype [40]. The gene controlling the chicken crest trait may be located in the HOXC cluster adjacent to the HOXC8 gene [41].…”
Section: Discussionmentioning
confidence: 99%
“…Whether it is simply functional redundancy or regional specificity is an interesting question. Hox genes represent the best example that elicit distinct developmental programs along the head-to-tail axis of animals and are the upstream signals of many Wnt proteins 56 , 57 , 58 , 59 , 60 , 61 . Whether distinct HOXs activate different WNTs and generate regional specific feather rachis is another interesting question.…”
Section: Discussionmentioning
confidence: 99%